2018
DOI: 10.1002/2017jd028161
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Responses of Hot Extremes to Historical Land Use and Cover Change Among the Selected CMIP5 Models

Abstract: Land use and cover change (LUCC) is an important anthropogenic forcing of the climate system. Previous studies have demonstrated that LUCC significantly impacts both mean and extreme temperatures. In this study, we explored the multimodel performance of simulating LUCC‐induced asymmetric effects on the different percentiles of maximum temperatures (Tmax) as well as the possible reasons for these effects using results from the fifth phase of the Coupled Model Intercomparison Project (CMIP5). Four state‐of‐art E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 77 publications
2
17
0
Order By: Relevance
“…Some regions with extensive historical LCC (Eurasia and North America) have experienced biophysical decreases in annual mean temperature of a magnitude similar to the concomitant increase in greenhouse gases (de Noblet-Ducoudré et al 2012). However, considerable disagreement is evident in model responses; most models show mid-latitude decreases of most hot extreme indices , Christidis et al 2013, Li et al 2018, Chen and Dirmeyer 2019, while other models simulate increases (Avila et al 2012, Findell et al 2017, Lejeune et al 2018, Li et al 2018, Chen and Dirmeyer 2019 in response to historical LCC. For instance, three out of four models of the 'land-use and climate, identification of robust impacts' (LUCID) intercomparison project simulated a decrease in extremely warm daytime temperatures over the northern mid-latitudes during summer due to historical LCC .…”
Section: Introductionmentioning
confidence: 99%
“…Some regions with extensive historical LCC (Eurasia and North America) have experienced biophysical decreases in annual mean temperature of a magnitude similar to the concomitant increase in greenhouse gases (de Noblet-Ducoudré et al 2012). However, considerable disagreement is evident in model responses; most models show mid-latitude decreases of most hot extreme indices , Christidis et al 2013, Li et al 2018, Chen and Dirmeyer 2019, while other models simulate increases (Avila et al 2012, Findell et al 2017, Lejeune et al 2018, Li et al 2018, Chen and Dirmeyer 2019 in response to historical LCC. For instance, three out of four models of the 'land-use and climate, identification of robust impacts' (LUCID) intercomparison project simulated a decrease in extremely warm daytime temperatures over the northern mid-latitudes during summer due to historical LCC .…”
Section: Introductionmentioning
confidence: 99%
“…Climate models (Arora and Montenegro 2011;Bala et al 2007; Davin and de Noblet-Ducoudré 2010) simulate a warming effect while observations (Alkama and Cescatti 2016;Burakowski et al 2018;Duveiller et al 2018;Li et al 2015;Schultz et al 2017;Wang et al 2018) point to cooling. Recent studies also suggest afforestation can impact temperature extremes (Findell et al 2017;Skinner et al 2018;Teuling et al 2010) although modeling of these processes is very uncertain (Avila et al 2012;Li et al 2018;Pitman et al 2012). Despite these uncertainties, the biophysical effects of afforestation on climate need to be considered, especially at local and regional scales where afforestation strategies are being implemented, to avoid risk of maladaptation (Anderson et al 2011;Bonan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the impacts on precipitation, which are more complex and difficult to validate, the relationship between deforestation and temperature has been extensively investigated using both observational datasets and modeling approaches 4 . In particular, recent studies have suggested that historical LULCC (namely deforestation) can significantly influence local high temperature extremes [5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Satellite-based observations show that cleared lands are warmer than nearby forest in daily maximum temperature during summer [12][13][14] . On the contrary, results from CMIP5 (Coupled Model Intercomparison Project Phase 5 15 ) and LUCID (land use and climate: identification of robust impacts 16,17 ) tend toward a summer daytime cooling over the middle latitudes as a result of documented historical deforestation 6,11 . The disagreement of model results with observations has been claimed to be associated with parameterization issues in current land surface models, such as the changes in partitioning of available energy between latent and sensible heat fluxes due to LULCC 6,8,11 .…”
mentioning
confidence: 99%